Seblang Ritual Performance of "Using Society"In Banyuwangi Regency (International Journal of Scientific Research and Management (IJSRM), 2017)
Ritual Seblang derived from pre-Hindu culture, dance form with trance / unconscious synonymous with offering something to disa village. Using public dipercayaoleh Seblang ritual function of sacred and profane. Seblang is the oldest culture in Banyuwangi and is a sacred dance man can communicate with spirits unseen or danyang with the aim of getting cosmic harmony. If the ritual is not implemented, then disharmonies will occur and the ecological balance can be disturbed as crop failures and plague pagebluk.As the village clean ceremonies, rituals Seblang carried out with the aim of cleaning the village of delicate creatures are dangerous, where the existing dish dedicated to disa village. Based on the above description, the problems in this paper, as follows: 1). how the implementation of the performing arts in the District Glagah Seblang Banyuwangi?; 2). how the community functions for the District Seblang show Glagah?. With qualitative methods and methods of history, the results of this study, is a community in the district Glagah Using the geographical conditions that support for an agrarian economy that characterizes their culture. Ritual Performances Seblangan has been a tradition since 17-21 century still held. Tradition has the potential to become a tourist village supporter Using in Banyuwangi. Can be summarized as follows: 1) .Pelaksanaan seblangan ritual performance is supported by the geographical potential suitable for agricultural farming, and public confidence in the customs, traditions and culture handed down by their ancestors still retained by the people in the District Using Glagah; 2). Bakungan Seblang rituals conducted in Dzulhijjah or after the Eid al-Adha is held collectively, becomes a medium between people with supernatural / spirits, remain rooted in the sacred. In the rite of the meaning of reality presented in society (social meaning). Rite instrumental strengthen the collective sense of rootedness. Seblang ritual religious serves as an expression of gratitude, starting reinforcements against any disaster that might happen. Also functioning mechanical and organic solidarity Using community. In addition, profane thus serving the entertainment attractions.